2018
DOI: 10.1002/adtp.201800079
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Biomineralization‐Based Engineering

Abstract: In nature, the biomineralization processes of living organisms produce a wide range of organic-inorganic hybrid materials to achieve various functions. In particular, egg shells can provide extra protection for embryos and maintain air exchange. Inspired by such phenomena, it is assumed that the engineering of organisms with biomimetic materials can lead to significant improvement in organism function. This review summarizes recent progress in biomineralization-based techniques for organism engineering, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 191 publications
(308 reference statements)
1
11
0
Order By: Relevance
“…In addition, it points out that proteins occluded inside the crystals are possibly more resistant to high temperatures, in agreement with previous concepts that amino acids are well preserved in shells or fossils (Abelson, 1957). Coincident with this idea, the encapsulation of organisms such as viruses, bacteria, yeast, and cells by biomineralized structures has been explored in the past 15 years (Liu et al, 2016;Wang et al, 2018). These studies have shown enhanced stability for preserving the encapsulated organisms (Liu et al, 2016;Wang et al, 2018).…”
Section: Possible Indications Limitations and Outlooksupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, it points out that proteins occluded inside the crystals are possibly more resistant to high temperatures, in agreement with previous concepts that amino acids are well preserved in shells or fossils (Abelson, 1957). Coincident with this idea, the encapsulation of organisms such as viruses, bacteria, yeast, and cells by biomineralized structures has been explored in the past 15 years (Liu et al, 2016;Wang et al, 2018). These studies have shown enhanced stability for preserving the encapsulated organisms (Liu et al, 2016;Wang et al, 2018).…”
Section: Possible Indications Limitations and Outlooksupporting
confidence: 81%
“…Coincident with this idea, the encapsulation of organisms such as viruses, bacteria, yeast, and cells by biomineralized structures has been explored in the past 15 years (Liu et al, 2016;Wang et al, 2018). These studies have shown enhanced stability for preserving the encapsulated organisms (Liu et al, 2016;Wang et al, 2018). 2) Proteins can be preserved for a long time in biominerals such as teeth, bones, and shells.…”
Section: Possible Indications Limitations and Outlookmentioning
confidence: 99%
“…The results showed that OA exhibited clear cytotoxicity on tumor cells in a time-dependent manner, while much lower cytotoxicity was observed on normal cells, suggesting that OA could specifically infect tumor cells (see Figure S1 in the Supporting Information). OA is negatively charged at physiological pH, because of the abundant carboxyl residues from anionic peptides on its surface. Hence, Mn 2+ and Ca 2+ could absorb onto OA with the addition of MnCl 2 and CaCl 2 . In addition, the intrinsically anisotropic structures of viruses could also act as attractive biotemplates for biomineralization. , Therefore, a MnCaCs mineral shell spontaneously formed around OA after the following addition of Na 2 CO 3 under physiological conditions (OA@MnCaCs).…”
Section: Resultsmentioning
confidence: 99%
“…Biomineral-based skeletal structures are seen at all length scales ranging in nature from the nano (virus and bacteria) to the micro (diatoms, coccolithophores) to the macro (several meters long whale bones) levels. The mechanisms controlling and affecting biomineralization remain hotly debated with both basic science implications as well as direct application in the field of biomimetics. , Detailed knowledge about biomineralization is useful for abstract concepts of modern material science, nanotechnology, and biologically inspired materials chemistry. , …”
Section: State Of the Artmentioning
confidence: 99%